Congenital Diaphragmatic Hernia Presenting with Tension Pneumothorax in a 3-Year-Old Boy - Maren Friederike Balks; Jan-Hendrik Gosemann; Ina Sorge; Martin Lacher; Franz Wolfgang Hirsch (Georg Thieme Verlag KG, 2018)
We report the case of a 3-year-old boy who presented with an upper respiratory tract infection and severe dyspnea. A chest X-ray revealed a left-sided tension pneumothorax with mediastinal shift and suspected enterothorax. After thoracic computed tomography (CT) scan, a chest tube was inserted, which drained fluid which had the same consistency and color as the one derived from the nasogastric (NG) tube. The boy underwent diagnostic laparoscopy for suspected bowel perforation, which confirmed a left-sided Bochdalek hernia with herniation of the viscera into the chest. After repositioning of the herniated organs into the abdomen, a gastric perforation was identified and repaired. This case demonstrates that the cause of a tension pneumothorax in an infant may be a rare combination of congenital diaphragmatic hernia (CDH) and perforation of a visceral hollow organ.